Improving Students’ Dyscalculia Numeracy Ability Using Learning Media Colored Bead Montessori - Damri, Damri; Amalia, Rizqoh; Engkizar, Engkizar; Efendi, Efendi; Ramadhani, Ramadhani; Asril, Zainal (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
This study aims to investigate the effects of colored bead Montessori learning media to students’ numeral thinking skills none of the elementary schools (SD) in Padang, Indonesia. This study used a quantitative method with a single-subject research approach, the research data was taken from a student with dyscalculia through fifteen direct lessons using colored bead Montessori learning media. Data were analyzed by using visual graphical analysis tool descriptively were analyzed descriptively using visual graphical analysis tools. The results of this study showed that the use of colored bead Montessori learning media based on the analysis can actually improve the numeracy skills of students with dyscalculia in learning. This improvement is proved by, at first the students' scores were 2, 4, 4, 4, this was the value before the researcher used the media. Furthermore, after the researcher did seven times direct treatment, it was found that the students' scores increased to 10, 13, 15, 18, 20, 20, 20, even students were able to obtain self-evaluation scores with numbers 20, 20, 20, 20. The results of this study proved that the use of colored bead Montessori media has been able to improve the numeracy skills of students in learning. Referring to the results of this research, colored bead Montessori can be used as an alternative media in learning numeracy skills of students with dyscalculia none of the elementary schools.